Impact of donor-specific antibodies on long-term graft survival with pediatric liver transplantation - Schotters, Felicitas Leonie (World J Hepatol, 2021)
BACKGROUND: In a previous paper, we reported a high prevalence of donor-specific antibody (DSA) in pediatric patients with chronic rejection and expressed the need for confirmation of these findings in a larger cohort. AIM: To clarify the importance of DSAs on long-term graft survival in a larger cohort of pediatric patients. METHODS: We performed a retrospective analysis of 123 pediatric liver transplantation (LT) recipients who participated in yearly follow-ups including Luminex testing for DSA at our center. The cohort was split into two groups according to the DSA status (DSA-positive n = 54, DSA-negative n = 69). Groups were compared with regard to liver function, biopsy findings, graft survival, need for re-LT and immunosuppressive medication. RESULTS: DSA-positive pediatric patients showed a higher prevalence of chronic rejection (P = 0.01), fibrosis (P < 0.001) and re-transplantation (P = 0.018) than DSA-negative patients. Class II DSAs particularly influenced graft survival. Alleles DQ2, DQ7, DQ8 and DQ9 might serve as indicators for the risk of chronic rejection and/or allograft fibrosis. Mean fluorescence intensity levels and DSA number did not impact graft survival. Previous episodes of chronic rejection might lead to DSA development. CONCLUSION: DSA prevalence significantly affected long-term liver allograft performance and liver allograft survival in our cohort of pediatric LT. Screening for class II DSAs in combination with assessment of protocol liver biopsies for chronic antibody-mediated rejection improved early identification of patients at risk of graft loss.